The relationship between fingerprint patterns and intelligence qoutient of dental students batch 2021 of Baiturrahmah University : Hubungan pola sidik jari dengan intelligence qoutient mahasiswa kedokteran gigi angkatan 2021 Universitas Baiturrahmah - Rizkiani, Erdina Wira; Firdaus; Iswani, Resti; Sari, Widya Puspita; Surya, Leny Sang (Makassar Dental Journal PDGI Makassar, 2025)
Intelligence quotient (IQ) and fingerprint pattern (FPP) are related because during the intrauterine period, brain and PSJ forma-tion occur almost simultaneously. Normal or abnormal genetic messages during this period will affect the brain and FPP. This study discusses the relationship between FPP and IQ level in 2021 students of the Faculty of Dentistry, Baiturrahmah Universi-ty. Analytical quantitative research was conducted on students of the Faculty of Dentistry Class of 2021 as many as 53 sam-ples with random sampling technique. Univariate analysis is presented in the form of frequency distribution, bivariate analysis using the chi-square test and data processing using the computerised SPSS v.25.0. The study showed that the most FPPs were loops, namely 37 people, the most IQ level was average, namely 40 people. It was concluded that there was no relationship between FPP and IQ level in 2021 dental students at Baiturrahmah University.